The Influence of Lifestyle on Hijapedia Purchase Decisions Moderated By Religiusity Variables - RR Wening Ken Widodasih; Langgeng Sri Handayani; Kurbandi SBR (Indonesian Journal of Business Analytics, 2023)
This research was conducted at  Hijapedia SMEs in Bekasi district. This study aims to examine the influence of lifestyle on purchasing decisions, by considering the religiosity as a moderating variable. The results of this study are Lifestyle has a significant effect on Purchase Decision with t-statistic 1.116> 1.96, while Religiosity has a significant effect on Purchase decision with t-statistic 2.402> 1.96, and religiosity as a moderating variable does not strengthen Lifestyle on Purchase Decision with t-statistic 0.061 < 1.96. This means that women who are more religious tend to consider religious values more in choosing hijab products, although lifestyle still plays an important role in purchasing decisions. This research contributes for marketers to the understanding of women's consumer behavior.